An aggregation function to solve multicriteria ranking problem involving several decision makers - Savadogo, Zoinabo; M. Ngoie, Ruffin-Benoît; Ulungu E.-L., Berthold; Somé, Blaise (International Journal of Applied Mathematical Research, 2014)
Multiple Criteria Decision Aiding (MCDA) has been studied in a single decision maker framework for a long time. Nowadays, the need to take into account several conflicting opinions handled by several decisions makers arises. So, researchers are interested with multicriteria problems involving several decision makers. In this context, to solve ranking problem, we develop an aggregation model of several additive value functions. Comparisons with a derivative ELECTRE I method is done on numerical data. Clearly, it appears that the proposed aggregation function is better according to calculation complexity and computation time. Way for further research in this field is proposed.